2021
DOI: 10.1088/0256-307x/38/7/077401
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Superconducting Thin Films of Infinite-Layer Nickelate Nd0.8Sr0.2NiO2

Abstract: The recent observation of superconductivity in thin films of infinite-layer nickelate Nd0.8Sr0.2NiO2 has received considerable attention. Despite the many efforts to understand the superconductivity in infinite-layer nickelates, a consensus on the underlying mechanism for the superconductivity has yet to be reached, partly owing to the challenges with the material synthesis. Here, we report the successful growth of superconducting infinite-layer Nd0.8Sr0.2NiO2 films by pulsed laser deposition and soft chemical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…For IL nickelates, a close relation and possible analogy to cuprate superconductors was suggested already in 1999 [11], and since the first discovery of superconductivity in the IL nickelate (Nd,Sr)NiO 2 [12], the observation of superconductivity has been confirmed [13][14][15] and extended to (Pr,Sr)NiO 2 [16], (La,Sr)NiO 2 [17], (La,Ca)NiO 2 [18], and Nd 6 Ni 5 O 12 [19]. Furthermore, a recent work reported superconductivity not only for films grown on SrTiO 3 substrates but also on LSAT [20], which provides enough evidence to consider thin-film nickelates as a novel class of superconductors.…”
Section: Introductionmentioning
confidence: 89%
“…For IL nickelates, a close relation and possible analogy to cuprate superconductors was suggested already in 1999 [11], and since the first discovery of superconductivity in the IL nickelate (Nd,Sr)NiO 2 [12], the observation of superconductivity has been confirmed [13][14][15] and extended to (Pr,Sr)NiO 2 [16], (La,Sr)NiO 2 [17], (La,Ca)NiO 2 [18], and Nd 6 Ni 5 O 12 [19]. Furthermore, a recent work reported superconductivity not only for films grown on SrTiO 3 substrates but also on LSAT [20], which provides enough evidence to consider thin-film nickelates as a novel class of superconductors.…”
Section: Introductionmentioning
confidence: 89%
“…It was also shown that parameters such as the laser spot size or the target history could also play an important role in obtaining single phase perovskite films. However, the synthesis of hole doped nickelates is particularly challenging, not only due to the instability of highvalence Ni itself but also because of the competition between the perovskite phase and Ruddelsden-Popper phases [26,27]. These two factors are the main obstacles to obtain single-phase perovskite films.…”
Section: Epitaxial-growth Aspectsmentioning
confidence: 99%
“…The goal is to selectively remove one-third of oxygens (i.e., one full plane of apical oxygens) and thereby stabilize the oxygen poorer infinite-layer phase. The literature diverges regarding the exact conditions for this process, but it typically has to be performed between 200 and 360 °C for several hours [6,7,10,27,28]. In the ideal case, X-ray diffraction then reveals the complete transformation of the perovskite phase into the infinitelayer phase, with a characteristic shift of the (002) peak position to higher angles (~54 °) signalling the contraction of the out-of-plane lattice constant, an intense (001) peak (its absence or reduced intensity is again the signature of spurious phases) and Laue fringes, attesting of the good structural coherence of the infinitelayer phase in the growth direction [9,27,28].…”
Section: Epitaxial-growth Aspectsmentioning
confidence: 99%
“…The discovery of nickel superconductors [1] has attracted renewed attention to superconductivity in strongly correlated electron systems [2][3][4][5][6][7]. So far, superconductivity has been found in film samples of doped infinite-layer nickelates RNiO 2 (R = Nd, Pr, and La) [1,[8][9][10][11][12][13][14][15][16] and a quintuple-layer nickelate Nd 6 Ni 5 O 12 [17]. Although the nature of the superconductivity is largely unknown, the pairing mechanism is likely to be unconventional: Theoretically, a phonon calculation for NdNiO 2 has shown that the electron-phonon coupling is too weak to explain the superconductivity with a transition temperature on the order of 10 K [18].…”
Section: Introductionmentioning
confidence: 99%